On the perception of the poem “Almotanabi” by Adam Mickiewicz - Novruzov, Rafig; Novruzova, Gulnar (Abdul Media Literasi, 2025)
This article is devoted to the translation of the poem “Almotanabi” (given in the author’s writing) by the famous European poet Adam Mickiewicz into Polish, made from the text of Granger de Lagrange’s translation of the French language. The very fact of translation from Arabic into French makes it possible to study this poem from various perspectives: a comparative analysis of the French translation and the original Arabic text, and an analysis of the text that clarifies the motives for referring to this work and the corresponding interpretations of the author. Our research focuses on the latter type, which aims to identify details of interpretation that clarify their similarity or difference with the original. Considering the fact that every translation is an inevitable transformation of the text on the part of the translator, Mickiewicz’s translation should be considered both a translation and a stylization of the source text. The analysis shows that, despite his sufficient knowledge of the Arabic author and his qasida, he could not avoid the perception of the text by the European reader, which allows us to regard his translation as a West-Eastern synthesis in the spirit of the famous German poet I.V. Goethe.